SDF-1α/MicroRNA-134 Axis Regulates Nonfunctioning Pituitary Neuroendocrine Tumor Growth via Targeting VEGFA - Wang, Xiaoyu; Fang, Yuanjian; Zhou, Yunxiang; Guo, Xiaoming; Xu, Ke; Li, Chenguang; Zhang, Jianmin; Hong, Yuan (Frontiers in Endocrinology, 2020)
Background: Nonfunctioning pituitary neuroendocrine tumor (NF-PitNET) is difficult to resect. Except for surgery, there is no effective treatment for NF-PitNET. MicroRNA-134 (miR-134) has been reported to inhibit proliferation and invasion ability of tumor cells. Herein, the mechanism underlying the effect of miR-134 on alleviating NF-PitNET tumor cells growth is explored. Methods: Mouse pituitary αT3-1 cells were transfected with miR-134 mimics and inhibitor, followed by treatment with stromal cell-derived factor-1α (SDF-1α) in vitro. MiR-134 expression level: we used quantitative real-time PCR (qRT-PCR) to detect the expression of miR-134. Cell behavior level: cell viability and invasion ability were assessed using a cell counting kit-8 (CCK8) assay and transwell invasion assay respectively. Cytomolecular level: tumor cell proliferation was evaluated by Ki-67 staining; propidium iodide (PI) staining analyzed the effect of miR-134 on cell cycle arrest; western blot analysis and immunofluorescence staining evaluated tumor migration and invasive ability. Additionally, we collected 27 NF-PitNET tumor specimens and related clinical data. The specimens were subjected to qRT-PCR to obtain the relative miR-134 expression level of each specimen; linear regression analysis was used to analyze the miR-134 expression level in tumor specimens and the age of the NF-PitNET population, gender, tumor invasion, prognosis and other indicators. Results: In vitro experiment, miR-134 was observed to significantly inhibit αT3-1 cells proliferation characterized by inhibited cell viability and expressions of vascular endothelial growth factor A (VEGFA) and cell cycle transition from G1 to S phase (P < 0.01). VEGFA was verified as a target of miR-134. Additionally, miR-134-induced inhibition of αT3-1 cell proliferation and invasion was attenuated by SDF-1α and VEGFA overexpression (P < 0.01). In primary NF-PitNET tumor analysis, miR-134 expression level was negatively correlated with tumor invasion (P =0.003). Conclusion: The regulation of the SDF-1α/miR-134/VEGFA axis represents a novel mechanism in the pathogenesis of NF-PitNETs and may serve as a potential therapeutic target for the treatment of NF-PitNETs.